Multivalent Functions Involving Srivastava-Tomovski Generalization of the Mittag-Leffler Function Defined in the Nephroid Domain - ÇETİNKAYA, ASENA (Publ House Bulgarian Acad Sci., 2021)
In this paper, we introduce a new class of multivalent functions defined by generalized Mittag-Leffler function bounded by Nephroid domain. We investigate majorization properties for this class. Moreover, using the technique of Briot-Bouquet differential subordination, we obtain some subordination properties.
Keywords: Mittag-leffler Function; Differential Subordination; Majorization; Nephroid Domain